Presbycusis Disrupts Spontaneous Activity Revealed by Resting-State Functional MRI - Chen, Yu-Chen; Chen, Huiyou; Jiang, Liang; Bo, Fan; Xu, Jin-Jing; Mao, Cun-Nan; Salvi, Richard; Yin, Xindao; Lu, Guangming; Gu, Jian-Ping (Frontiers in Behavioral Neuroscience, 2018)
Purpose: Presbycusis, age-related hearing loss, is believed to involve neural changes in the central nervous system, which is associated with an increased risk of cognitive impairment. The goal of this study was to determine if presbycusis disrupted spontaneous neural activity in specific brain areas involved in auditory processing, attention and cognitive function using resting-state functional magnetic resonance imaging (fMRI) approach. Methods: Hearing and resting-state fMRI measurements were obtained from 22 presbycusis patients and 23 age-, sex-, and education-matched healthy controls. To identify changes in spontaneous neural activity associated with age-related hearing loss, we compared the amplitude of low-frequency fluctuations (ALFF) and regional homogeneity (ReHo) of fMRI signals in presbycusis patients versus controls and then determined if these changes were linked to clinical measures of presbycusis. Results: Compared with healthy controls, presbycusis patients manifested decreased spontaneous activity mainly in the superior temporal gyrus (STG), parahippocampal gyrus, precuneus, and inferior parietal lobule as well as increased neural activity in the middle frontal gyrus (MFG), cuneus, and postcentral gyrus. A significant negative correlation was observed between ALFF/ReHo activity in the STG and average hearing thresholds in presbycusis patients. Increased ALFF/ReHo activity in the MFG was positively correlated with impaired Trail-Making Test B (TMT-B) scores, indicative of impaired cognitive function involving the frontal lobe. Conclusions: Presbycusis patients have disrupted spontaneous neural activity reflected by ALFF and ReHo measurements in several brain regions; these changes are associated with specific cognitive performance and speech/language processing. These findings mainly emphasize the crucial role of aberrant resting-state ALFF/ReHo patterns in presbycusis patients and will lead to a better understanding of the neuropathological mechanisms underlying presbycusis.